Pendampingan Kegiatan Penelitian Tindakan Sekolah di SDI Bhoanawa 2 Ende - Nining Sar'iyyah; Yuliani Sepe Wangge; Aurelius Fredimento; Gregorius Sebo Bito (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
This service activity aims to increase the understanding of the principal of SDI Bhoanawa2 through school action research assistance activities. The mentoring process was carried out intensely from February 2022 to May 2022. Mentoring was carried out using a gradual discussion method and the results of this activity were increasing the principal's understanding of school action research and producing products in the form of reports on school action research results and publication of articles in one of the one national journal is not accredited.